2022
DOI: 10.1080/10717544.2022.2058651
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo characterization of Entacapone-loaded nanostructured lipid carriers developed by quality-by-design approach

Abstract: Entacapone, a reversible catechol-o-methyl transferase inhibitor, is used to enhance the action of dopamine agonists by reducing their metabolism and the ‘Wearing-off’ effects associated with long-term use in the treatment of Parkinson's disease. It is used as an adjunct to levodopa/Carbidopa therapy. Due to limited dissolution and first-pass clearance, it suffers low and variable bioavailability issues. To overcome this problem, the present study aims to explore the potential of nanostructured lipid carriers … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The negative effect of increasing sonication time on EE % was similarly reported after piperine NLCs formulation ( Zafar et al, 2021 ). Also, comparable results were declared by Agrawal et al ( Agrawal et al, 2022 ) who found that EE% of entacapone in the formulated NLCs decreased with increasing sonication time.…”
Section: Resultssupporting
confidence: 88%
“…The negative effect of increasing sonication time on EE % was similarly reported after piperine NLCs formulation ( Zafar et al, 2021 ). Also, comparable results were declared by Agrawal et al ( Agrawal et al, 2022 ) who found that EE% of entacapone in the formulated NLCs decreased with increasing sonication time.…”
Section: Resultssupporting
confidence: 88%
“…Inadequate membrane permeability, insu cient aqueous solubility in gastrointestinal uids, and the rst-pass effect can all contribute to suboptimal bioavailability [12][13][14]. According to the biopharmaceutics classi cation system [15][16][17][18][19][20], Entacapone is categorized as a class IV medication. Reports indicate that nanosized formulations improve the permeability and solubility of water while also preventing rst-pass effects.…”
Section: Introductionmentioning
confidence: 99%
“…Up till now, no perfect treatment exists for management of PD and therapy is mainly focusing on the relief of symptoms [ 4 ]. The current treatment includes the use of dopamine agonists (levodopa) and monoamine oxidase (MAO) inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…The current treatment includes the use of dopamine agonists (levodopa) and monoamine oxidase (MAO) inhibitors. Nevertheless, as the disease worsens, the efficacy of the conventional therapy decreases producing end-of-dose adverse effects called wear-off symptoms characterized by the recurrence of both motor and non-motor manifestations [ 4 ]. Recently, the focus on discovering phytomedicines has been growing considerably as a method of finding safer alternatives to synthetic drugs.…”
Section: Introductionmentioning
confidence: 99%